2020
DOI: 10.1021/acs.macromol.9b02177
|View full text |Cite
|
Sign up to set email alerts
|

High Molecular Weight Biodegradable Poly(ethylene glycol) via Carboxyl-Ester Transesterification

Abstract: Poly(ethylene glycol) (PEG) is widely used for covalent conjugation with therapeutic molecules to prolong their biocirculation time. This effect can be further improved by increasing the molecular weight of PEG. However, because of the lack of effective degradation mechanisms, PEG with a molecular mass over 10 kDa is hardly excreted from the body, thus accumulating in the liver and kidneys which increases the risk of toxicity. Herein, biodegradable PEGs were synthesized by linking PEG backbones with ester bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 65 publications
1
31
0
1
Order By: Relevance
“…All the above characterization studies verify the proposed polymerization mechanism (Scheme 1, This work). To further verify this proposed mechanism, a model reaction between BPO and bromobenzene or p-methylbromobenzene was carried out under Barbier reaction conditions at room temperature without an activator for 12 h. Triphenylmethanol and 4-4′-dimethyl triphenylmethanol were successfully obtained and confirmed by 1 H and 13 C NMR (Fig. S5-S8 †).…”
Section: Room-temperature Barbier Single Atom Polymerizationmentioning
confidence: 82%
See 1 more Smart Citation
“…All the above characterization studies verify the proposed polymerization mechanism (Scheme 1, This work). To further verify this proposed mechanism, a model reaction between BPO and bromobenzene or p-methylbromobenzene was carried out under Barbier reaction conditions at room temperature without an activator for 12 h. Triphenylmethanol and 4-4′-dimethyl triphenylmethanol were successfully obtained and confirmed by 1 H and 13 C NMR (Fig. S5-S8 †).…”
Section: Room-temperature Barbier Single Atom Polymerizationmentioning
confidence: 82%
“…[2][3][4][5][6][7][8][9][10][11] For example, polyesterification and polyamidation are based on the corresponding esterification and amidation reactions, resulting in significant polyesters and polyamides, e.g., polyethylene terephthalate (PET) and nylon. [12][13][14] A series of coupling polymerizations are based on the corresponding Stille-, Suzuki-, Kumada-coupling reactions, etc. [15][16][17] Living ring-opening metathesis polymerization is based on the olefin metathesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to a number of factors including trace monomer impurities, side reactions and mass transfer limitations. [22] However, such results are amenable to further optimization. Demarteau et al [14b] have previously reported PEA (1)(2), achieving comparable M n with narrower dispersities (Đ = 1.34-1.46).…”
Section: Production Of Poly(ester-amide)s (Pea)mentioning
confidence: 99%
“…Degradable polymers containing cleavable moieties within their backbone can reduce their molecular weight overtime, until they are shortened to units small enough to be exerted by the body. A prominent example of degradable synthetic polymer is PLA and its corresponding PGA, which are polyesters that undergo hydrolysis in mild acidic conditions or can be cleaved ‘on demand’ by an esterase [ 103 ]. Such polyesters are obtained via ring-opening polycondensation [ 104 ].…”
Section: Synthetic Criteria For Hydrogel Productionmentioning
confidence: 99%